2018
DOI: 10.1002/ajoc.201700626
|View full text |Cite
|
Sign up to set email alerts
|

Highly Selective and Sensitive 2‐(2′‐Hydroxyphenyl)benzothiazole‐Based Turn‐On Fluorescent Probes for Detecting and Imaging Bisulfite in Living Cells

Abstract: Bisulfite (HSO 3 À )i so ne of the main forms of sulfur dioxide in physiological systems. Two2 -(2'-hydroxyphenyl)benzothiazole-derived fluorescentp robes bearinganitroolefin moiety were designed based on the intramolecular charge transfer (ICT) effect and excited-state intramolecular proton transfer (ESIPT) mechanism to afford af luorescent turn-on response specifically in the present of HSO 3 À ions. Owing to the remarkable ICT effect from hydroxy group to the nitro group, the probese xhibit extremelyw eakf … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 30 publications
0
7
0
1
Order By: Relevance
“…As illustrated in Scheme , the probe was designed based on the ICT process using HBT and EMBI as the donor and acceptor, respectively, which exhibited essentially a peak at 461 nm assigned to HBT-like emission , via a weak ESIPT effect, and that at 625 nm owing to an efficient ICT effect. We anticipated that HSO 3 – /SO 3 2– anions might selectively attack the unsaturated vinyl group of probe HBT-EMBI in a manner that could interrupt the π-conjugation and inactivate the electron withdrawal of the EMBI moiety, thereby dramatically diminishing the ICT effect; thus, a strong ESIPT process would be observed, which would result in an improved fluorescence signal of the HBT chromophore at 461 nm, but a decreased fluorescence signal at 625 nm.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As illustrated in Scheme , the probe was designed based on the ICT process using HBT and EMBI as the donor and acceptor, respectively, which exhibited essentially a peak at 461 nm assigned to HBT-like emission , via a weak ESIPT effect, and that at 625 nm owing to an efficient ICT effect. We anticipated that HSO 3 – /SO 3 2– anions might selectively attack the unsaturated vinyl group of probe HBT-EMBI in a manner that could interrupt the π-conjugation and inactivate the electron withdrawal of the EMBI moiety, thereby dramatically diminishing the ICT effect; thus, a strong ESIPT process would be observed, which would result in an improved fluorescence signal of the HBT chromophore at 461 nm, but a decreased fluorescence signal at 625 nm.…”
Section: Resultsmentioning
confidence: 99%
“…Given the above-mentioned considerations, a ratiometric fluorescent probe named 2-(2′-hydroxyphenyl)­benzothiazole-3-ethyl-1,1,2-trimethyl-1 H -benzo­[ e ]­indolium (HBT-EMBI) (Scheme ), based on 2-(2′-hydroxyphenyl)­benzothiazole (HBT) and a hemicyanine unit of 3-ethyl-1,1,2-trimethyl-1 H -benzo­[ e ]­indolium (EMBI), was designed for sensing HSO 3 – /SO 3 2– via an addition reaction. In the structure of HBT-EMBI, the HBT unit is a typical ESIPT fluorophore with many excellent optical properties except short-wavelength emission spectra . By contrast, the introduction of the EMBI unit as a terminal group could efficiently increase the emission wavelength of HBT to the far-red region at 625 nm via the ICT process.…”
Section: Introductionmentioning
confidence: 99%
“…Wang et al . [ 48 ] of Northwest University (Xi'an China) demonstrated that the probe could quantitatively detect HSO 3 − anions, and that HSO 3 − could react with the nitro olefin part of the probe to produce new compounds based on the speculated mechanism of the probe's recognition of biothiols (Scheme 2). That is, sulfhydryl groups in biothiols (GSH/Hcy/Cys) could be used as nucleophiles and react with the nitro olefin part of the probe in an electrophilic addition reaction, which generated new compounds and destroyed the push–pull electron effect of the probe molecules, blocking the intramolecular charge transfer (ICT)effect of the probe, and releasing a blue fluorescence signal.…”
Section: Resultsmentioning
confidence: 99%
“…Compound 2 (0.2 g, 0.78 mmol) and ammonium acetate (60 mg, 0.78 mmol) were stirred and dissolved in 40 ml nitromethane, and then refluxed at 100°C. [ 48,49 ] The reaction process was monitored using thin‐layer chromatography (TLC) and, after 6 h, the basic reaction was completed. The reaction was cooled to room temperature and most organic solvents removed by vacuum distillation.…”
Section: Methodsmentioning
confidence: 99%
“…有别于苯并吡嗪, 其吡嗪 环两侧存在两个苯环, 共轭程度更大, 是良好的荧光发 色 团 , 可 设 计 、 合 成 荧 光 探 针 分 子 , 用 于 金 属 离 子 [111] 、阴离子 [112] 和中性分子 [113] 备 2,3-二氨基吩嗪 65 [114] , 再与芳香醛缩合 [115] , 如西北 师范大学魏太保课题组 [116] 制备的能连续检测 Fe 3+ 、 [117] . Khurana 课题 组 [118] 制备的探针 67 (Scheme 24), 在 0.5 mol [39,82] 、pH [19,46] 以及 溶液中同时含多种离子(Hg 2+ -Cu 2+ [59] 、Cu 2+ -Cd 2+ [96] 等) 的分析物检测, 在生物体内 [27,31] 与纯水相介质 [21,108] 的 检测应用亦有报道. 由于其特有的大共轭结构, 含 N、 O、S 等杂原子结合位点的存在, 以及其芳环上特定位 置 [68,75] 可设计发生一系列化学反应而引入功能性基团.…”
Section: 吩嗪类荧光探针unclassified